Plant Connections Leader’s Guide—Lesson 3: What Makes Plants Grow? - Janice Easton; Deborah J. Glauer (EDIS, 2015)
This revised document is the third lesson of the Kids Growing with Plant Connections Leader’s Guide. It is part of the 4-H Plant Connections Curriculum, which is aimed at educating youth about the basics of horticulture. In this guide, youth will be exposed to information on plants and the plant kingdom. Written by Janice Easton and Deborah J. Glauer, and published by the UF Department of 4-H Youth Development, January 2015.